2017
DOI: 10.15361/1984-5529.2017v45n2p123-129
|View full text |Cite
|
Sign up to set email alerts
|

Fungi as an alternative to produce essential fatty acids

Abstract: Fungi have the ability to produce essential fatty acids of the omega-3 family, what is of great scientific interest, since these microorganisms are capable of developing under varied conditions, making their production a viable alternative. Fatty acids are of great importance in human food due to their beneficial effects to the organism, such as reduction in the development of cardiovascular problems and other chronic-degenerative diseases. Currently, the main food source of omega-3 fatty acids is saltwater fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(32 reference statements)
1
3
0
Order By: Relevance
“…Moreover, the lipid profile of Arthrographis kalrae includes an omega-3 family member (docosahexaenoic acid polyunsaturated fatty acid, representing 4.6%). This finding was also supported by Francisco et al (2017), who reported the ability of many filamentous fungi to release essential fatty acids belonging to the omega-3 family, especially some Mortierella species that showed the ability to produce docosahexaenoic and eicosapentaenoic acids [25].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Moreover, the lipid profile of Arthrographis kalrae includes an omega-3 family member (docosahexaenoic acid polyunsaturated fatty acid, representing 4.6%). This finding was also supported by Francisco et al (2017), who reported the ability of many filamentous fungi to release essential fatty acids belonging to the omega-3 family, especially some Mortierella species that showed the ability to produce docosahexaenoic and eicosapentaenoic acids [25].…”
Section: Discussionsupporting
confidence: 52%
“…Also, extracellular metabolites of an endophytic Eurotium chevalieri isolate revealed potent broad spectrum antibacterial activity and inhibition of bacterial biofilms [21]. Based on the particular attention drawn on the biological activities of endophytic metabolites-specially, antimicrobial lipids in numerous studies [23][24][25][26]-the present study aimed at extracting fatty acids from an endophytic fungus isolated from Corandium sativium leaves and investigate the antivirulence activity of the extracted fatty acids combination against S. mutans.…”
Section: Introductionmentioning
confidence: 99%
“…The fungi, moreover, can grow up under different conditions, with consequent different production of lipids on the different substrates (26). Therefore, is important to identify parameters to optimize polyunsaturated fatty acid production (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…The main nutritional properties of lipids (or fats) come from fatty acids composition. In the food industry, supplementation or food enrichment with fatty acids of nutritional relevance produced by certain fungi species can minimize the risk factors related to, for example, cardiovascular or degenerative diseases (Francisco et al 2017). Most of the lipids produced in the fungal biomasses are mainly represented by fatty acids C16, C18, C18:1n-9, C18:2n-6, C18:3n-3, C20:3n-3, and C20:4n-6.…”
Section: Chemical Composition and Nutritive Value Of Fungal Biomassmentioning
confidence: 99%